Handle Region Peptide Ameliorating Insulin Resistance but Not β Cell Functions in Male Rats Neonatally Treated with Sodium L-Glutamate - Guo-shu Yin; Shao-da Lin; Dong-chuan Xu; Ru-qiong Sun; Kun Lin; Chu-jia Lin (International Journal of Endocrinology)
Handle region peptide (HRP), which was recognized as a blocker of (pro)renin receptor ((P)RR), may block the function of (P)RR. The aim of this study was to investigate the effect of HRP with a large dose of 1 mg/kg/d on glucose status in the rats treated neonatally with monosodium L-glutamate (MSG). At the age of 8 weeks, the MSG rats were randomly divided into MSG control group, HRP treated group with minipump (MSG-HRP group), losartan treated group (MSG-L group), and HRP and losartan cotreated group (MSG-HRP-L group) and fed with high-fat diet for 4 weeks. Losartan but not HRP increased the levels of insulin releasing and ameliorate glucose status although both losartan and HRP improved insulin sensitivity. On the one hand, both losartan and HRP decreased levels of pancreatic local Ang-II and NADPH oxidase activity as well as its subunits P22phox. On the other hand, losartan but not HRP decreased α-cell mass and number of PCNA-positive cells located periphery of the islets and decreased picrosirius red stained area in islets. HRP ameliorating insulin resistance but not β-cell functions leads to hyperglycemia in the end in male MSG rats, and the dual characters of HRP may partly account for the phenomenon.